The Emotional and Moral Basis of Rationality. Issue 13 (December 2013) - Boostrom, Robert
This chapter explores the basis of rationality, arguing that critical thinking tends to be taught in schools as a set of skills because of the failure to recognize that choosing to think critically depends on the prior development of stable sentiments or moral habits that nourish a rational self. Primary among these stable sentiments are the delight of recognition and the surprise of uncertainty. The creative act of imagination that sparks the delight of recognition is an invitation to begin rational enquiry. A flash of insight provides a motive for valuing the principle of truthfulness, which in turn provides a basis for a community of enquiry. While acknowledging that in the current climate of accountability-through-assessment there are good reasons for teachers to believe that the aim of nourishing the stable sentiments that support rationality is out of their reach, the chapter argues that students become independent rational reasoners only because they have lived in a community or classroom in which the surprise of uncertainty is valued more than a right answer, and the delight of recognition is more celebrated than a test score.